Hydrophobic Water Probed Experimentally at the Gold Electrode/Aqueous Interface. (16th March 2017) - Tong, Yujin; Lapointe, François; Thämer, Martin; Wolf, Martin; Campen, R. Kramer
Abstract: Quantitative description of reaction mechanisms in aqueous phase electrochemistry requires experimental characterization of local water structure at the electrode/aqueous interface and its evolution with changing potential. Gaining such insight experimentally under electrochemical conditions is a formidable task. The potential‐dependent structure of a subpopulation of interfacial water with one OH group pointing towards a gold working electrode is characterized using interface specific vibrational spectroscopy in a thin film electrochemical cell. Such free‐OH groups are the molecular level observable of an extended hydrophobic interface. This free‐OH interacts only weakly with the Au surface at all potentials, has an orientational distribution that narrows approaching the potential of zero charge, and disappears on oxidation of the gold electrode.